2012
DOI: 10.2308/accr-50378
|View full text |Cite
|
Sign up to set email alerts
|

Target Price Accuracy: International Evidence

Abstract: This paper shows that analysts exhibit differential and persistent ability to issue accurate target prices (TPs), and that institutional and regulatory differences across countries affect TP accuracy. Using a sample of 16 countries, we find that better past TP forecasters, analysts with higher forecasting experience, following more firms, country-specialized, and employed by a large broker issue more accurate TPs. Further, the country's institutional and regulatory factors, such as the accounting disclosure qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(36 citation statements)
references
References 54 publications
2
31
1
Order By: Relevance
“…Da and Schaumburg (2011) used the target price as a predictor of share mispricing variation in a sector. Bilinski et al (2013) point out that the target price reflects market expectations, and the forecasts related to them are higher than the forecasts based on price past performance (i.e. realized returns).…”
Section: Consensus Forecasts and Effects In The Securities Marketmentioning
confidence: 92%
See 4 more Smart Citations
“…Da and Schaumburg (2011) used the target price as a predictor of share mispricing variation in a sector. Bilinski et al (2013) point out that the target price reflects market expectations, and the forecasts related to them are higher than the forecasts based on price past performance (i.e. realized returns).…”
Section: Consensus Forecasts and Effects In The Securities Marketmentioning
confidence: 92%
“…Among the information generated by analysts, Bilinski et al (2013) highlight that the target prices reflect the estimate they make for the level of a company share price for a 12-month period, providing more easily-understood information for investment decisions. The authors observed that, on average, the accuracy of target prices is greater than the accuracy of share price forecast, and is correct or exceeds accuracy in 74.5% of the cases, and also presents superiority to other pricing measures, such as those obtained from the price-profit index of the sector and the return of market price of the 12 preceding months.…”
Section: Consensus Forecasts and Effects In The Securities Marketmentioning
confidence: 99%
See 3 more Smart Citations